Telephone lifestyle intervention to prevent diabetes in women with recent gestational diabetes mellitus attending the national health system: the LINDA-Brasil clinical trial - Bruce B Duncan; Maria Inês Schmidt; Paula A Bracco; Maria A Nunes; Kadhija A Cherubini; Cristina D Castilhos; Jainara Z Spagiari; Leony M Galliano; Ruben Ladwig; Fabricio B Del Vecchio; Anelita H M Del Vecchio; Michele Drehmer; et al. (BMJ Open)
Objectives To evaluate a postpartum telephone-based lifestyle intervention to prevent diabetes in high-risk women with recent gestational diabetes mellitus (GDM).Design Multicentre parallel randomised clinical trial.Setting Specialised antenatal clinics in the Brazilian National System.Methods Lifestyle Intervention for Diabetes Prevention After Pregnancy compared (1:1) postpartum telephone support for lifestyle changes with conventional care in women with recent GDM at substantial risk for diabetes. Randomisation started on 28 March 2015 and ended on 13 March 2020, with the onset of the COVID-19 pandemic. We used Cox regression to estimate HRs for diabetes and analysis of covariance adjusted for follow-up time to assess weight change.Outcomes The primary outcome was incident diabetes ascertained with blinded measurements of oral glucose tolerance tests. The secondary outcome was a change in measured weight.Results We enrolled 5323 women with GDM, 2735 (51%) being at high risk. After invitations, baseline assessment and exclusions, we assigned 466 women to intervention (231) or control (235) groups. Attendance was satisfactory (≥7/20 phone sessions) in 75%. Over an average follow-up of 29.7 (15.6) months, 142 (30.5%) women progressed to diabetes, 75 (32%) in the control and 67 (29%) in the intervention group. There was no reduction in the incidence of diabetes (HR=0.84; 0.60–1.19) and only a non-significant 0.97 kg less weight gain (p=0.09). Among the 305 women randomised more than 1 year before the COVID-19 pandemic, the intervention did not reduce the incidence of diabetes (HR=0.71; 0.48–1.04) despite a 2.09 kg (p=0.002) lesser weight gain.Conclusion The strategy to identify women with GDM at high risk proved valid, as women often gained weight and frequently developed diabetes. Over a 30-month follow-up, telephone support for lifestyle changes at postpartum did not reduce weight gain or diabetes incidence, although only 75% attended the minimum number of telephone sessions. The COVID-19 pandemic negatively impacted trial conduction.Trial registration number NCT02327286.